DAMPAK PENERAPAN TEKNOLOGI USAHATANI KEDELAI DI AGROSISTEM LAHAN KERING TERHADAP PENDAPATAN PETANI - Amar K Zakaria (Agrika, 2010)
Soybean is one of the strategic food commodities in Indonesia. The domestic production of soybean decreases continuously in line with the sharp decline of the planted area. 'lo fulfrll the domestic demand for soybean, impor was conducted. From ther farmers' side, the decrease in the planted area shows the low participation of farmers in planting the crop. Efforts to increase soybean production toward self-reliance area not only related with the technical aspects, but also strategies to strengthen farmer's parlicipation is soybean production increasing. The study was conducted in Garut District, West Java Province in May 2009 with using survey methods. The data was collected with interview toward 64 of farmer's sample. The result of study showed aboutthe level of farmer's o1' technology adoption is still under recommendation by government. In other hand, the activities of soybean farming in the farmer's level are shows feasibilities with R/C value is more one.   Key words farmers participation, upland, soybean farming, lechnology adoption